Hydroxychloroquine sulphate therapy of erosive oral lichen planus. (8th November 2018) - Yeshurun, Algit; Bergman, Reuven; Bathish, Naji; Khamaysi, Ziad
Abstract: Background/Objectives: Erosive oral lichen planus (LP) may be painful and debilitating. Symptomatic oral LP has been treated with a wide spectrum of topical and systemic therapies, but few have been evaluated in large series. Hydroxychloroquine is suggested to be effective in oral LP. Methods: Twenty‐one consecutive patients with erosive, biopsy‐confirmed oral LP were prescribed. hydroxychloroquine sulphate 400 mg/day. Symptomatic improvement was evaluated by means of a visual analogue scale into three groups: no change, moderate to marked improvement and complete remission. Results: Five (24%) patients obtained complete remission, 12 (57%) patients showed moderate to marked improvement, 3 (14%) patients did not improve at all and in one patient therapy was terminated after 1 month due to side effects. Response to therapy was observed after 2–4 months. Side effects which ultimately led to termination of therapy in three patients were elevated creatinine serum levels (after 1 month), visual field defects (after 8 months) and hyperpigmentation (after 24 months). Among six patients who responded to therapy, three flared on stopping. Conclusions: Hydroxychloroquine sulphate may be effective and relatively safe treatment for erosive oral LP.